Hydrologic remote sensing capacity building for sustainability and resilience - Hong, Yang; Zhang, Yu; Khan, Sadiq Ibrahim (IWA Publishing, 2017)
Environmental remote sensing plays a critical role in observing key hydrological components such as precipitation, soil moisture, evapotranspiration and total water storage on a global scale. This book reviews multiple remote sensing observations, the application of remote sensing in hydrological modeling, data assimilation and hydrological capacity building in emerging regions.